KESIAPSIAGAAN PESAWAT ANGKUT C-130 UNTUK PENANGGULANGAN BENCANA ALAM - Dwi Angga Bayu Hapsara; Andi Arman; Supri Abu (Universitas Perrtahanan Indonesia (UNHAN), 2023)
The involvement of the Indonesian National Armed Forces (TNI) in the task of humanitarian operations is very strategic. Among other things, this task was carried out by Squadron 31, namely by providing heavy and long-distance transportation equipment. Preparedness in humanitarian operations by providing 130 Hercules aircraft is an important aspect that supports the success of humanitarian operations. Research purposes. Analyzing the Preparedness of the 31 Squadron at Halim Perdanakusuma Air Base in the Provision of C-130 Transport Aircraft for Natural Disaster Management in Indonesia.Research methods using a descriptive qualitative approach with the selection of data sources using purposive sampling. Analysis of data from interviews, observations and documentation studies. Constructive analysis techniques with interactive procedures. Improvements to an effective humanitarian logistics management system to support the availability of spare parts in adequate and timely quantities for Squadron 31. Organizing training and education for aircraft crews for disaster management in accordance with the qualification standards of the National Disaster Management Agency (BNPB) as well as internationally involving the Indonesian Air Force and the Air Force and BNPB.